Effect of high calcium precursor (HCP) content on bonding strength of geopolymer concrete exposed at different curing temperatures / Mohd Najmudin Helmi Abu Bakar … [et al.] - Abu Bakar, Mohd Najmudin Helmi; Ahmad Zailani, Warid Wazien; Zuljar, Zulhaziq Khan; Mohd Apandi, Nazirah; Beddu, Salmia; Agustini, Ni Komang Ayu (Research Management Institute (RMI), 2023)
Geopolymer is a green cementitious binder that can be used to replace Portland cement binder and possesses exceptional physical, mechanical, and durability properties. Its mechanical properties such as bonding strength against the substrate were comparable to the Portland cement based repair products which can provide high durability and adhesive strength to the repaired structure. Geopolymer comprises two primary components which are the precursor and alkali activator. High Calcium Precursor (HCP) is the new repair material that was developed by Innovation Construction Materials (INCOM) Research Group to be used as a geopolymer’s precursor in Malaysia. In this research, the effect of HCP contents on the bonding strength of geopolymer concrete was assessed at different curing conditions. Based on the result, it found that 100 g of HCP gave an optimum bonding strength of 21.3 MPa after 28 days of normal curing. In addition, in this research, the bonding strength also was measured after the geopolymer/ substrate composite was exposed at different temperatures (60, 80, and 100 ⁰C). The bonding strength between HCP based geopolymer and the substrate does not significantly affected by the temperature’s exposure.